Land Use Cover Datasets and Validation Tools Validation Practices with QGIS - García-Álvarez, David; Camacho Olmedo, María Teresa; Paegelow, Martin; Mas, Jean François (Springer International Publishing : Imprint: Springer, 2022)
This open access book represents a comprehensive review of available land-use cover data and techniques to validate and analyze this type of spatial information. The book provides the basic theory needed to understand the progress of LUCC mapping/modeling validation practice. It makes accessible to any interested user most of the research community's methods and techniques to validate LUC maps and models. Besides, this book is enriched with practical exercises to be applied with QGIS. The book includes a description of relevant global and supra-national LUC datasets currently available. Finally, the book provides the user with all the information required to manage and download these datasets.